Endoscopic aqueductoplasty - Román, Guillermo; Morales, Luis Eloy; Canto, Alejandro (Revista Argentina de Neurocirugía, 2024)
Background. Endoscopic third ventriculostomy (ETV) has been increasingly used in the management of non-communicating hydrocephalus and is considered an effective procedure. Endoscopic aqueductoplasty (EA) together with EVT is proposed as an alternative with better results in selected cases. Objectives. To demonstrate the usefulness of aqueductoplasty as a neurosurgeon’s tool in the treatment of hydrocephalus. Case description. A 15-year-old female patient consulted for headache, nausea and vomiting. Physical examination showed instability and horizontal nystagmus. Computed tomography with hydrocephalus. Magnetic resonance imaging: aqueductal stenosis with supratentorial hydrocephalus with arachnoid cyst of the posterior fossa and tonsillar descent. Surgery. Approach through right Kocher point and neuroendoscope entry. The third ventricle was accessed through the foramen of Monro, performing a third ventriculocisternostomy and aqueductoplasty by insufflating a Fogarty catheter at the level of the Sylvian aqueduct. Endoscopic fenestration of the retrocerebellar cyst was also performed. Conclusion. AE may be a good alternative to simple EVT in selected patients.